Foreign policy change from the domestic perspective with the case of China - Zhou, Tong (The University of Edinburgh, 2024)
Due to its increasing importance in international politics, the evolving foreign policies of China have attracted the attention from scholars and policymakers globally. The objective of this study is to investigate the changes in China’s foreign policy since 2013 and examine the critical domestic factors that have contributed to this shift. The majority of the existing literature belongs to the neo-realism (e.g., Friedberg, 2015; Mearsheimer, 2006; Song, 2013; Yan, 2014), neoliberalism (e.g., Foot, 2017; Ikenberry, 2017; Kastner, Pearson and Rector, 2016), and constructivism schools (e.g., Legro, 2007; Qin, 2014; Uemura, 2015), and thus additional research from the domestic perspective is needed to better understand the impact of domestic factors on China’s foreign policy change. Moreover, more research on foreign policy change is needed for the current International Relations and Foreign Policy Analysis fields (Alden and Aran, 2017; Blavoukos and Bourantonis, 2017). This thesis adopts a qualitative research approach, mainly utilising case studies and document analysis. It also uses rational theory and constructivism theory to respectively analyse the One Belt and One Road Initiative case, the South China Sea case, and the Sino-US trade war case. By examining China’s foreign policy shift in light of its domestic context, this investigation could contribute to the research on China’s foreign policy, the influence of China’s rise on international politics, and foreign policy change.
An analysis on foreign policy change from the domestic perspective with the case of China
Keywords: Chinese Foreign policy; Domestic Politics; Foreign Policy Change